PARAOXONASE 3 GENE ALA99ALA POLYMORPHISM DISTRIBUTION IN BENINESE THREE ETHNIC POPULATIONS. - MISSIHOUN, ANTOINE ABEL HOUMÈNOU; SEGBO, JULIEN A. GAÉTAN; AGBANGLA, CLÉMENT (My University, 2016)
The paraoxonase has anti polymorphisms. The purpose of this study was to assess the genotypes distribution and allelic frequencies in paraoxonase paraoxonase 3 gene Ala99Ala polymorphism distribution of 228 subjects from populations, Polymorphism technique and compared with those in frequencies were 78.0 percent and 22.0 percent respectively frequencies were 98.0 percent and 2.0 percent respectively of percent and 33.0 percent respectively of of Mahi between Beninese PON3 gene polymorphisms distribution can be used as an for further investigation on the association of this polymorphism with the risk of inflammatory diseases.
Keywords: Single Nucleotide; Polymorphism; distribution; Population; Paraoxonase